Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran dan Akurasi Perencanaan Kas terhadap Tingkat Serapan Anggaran Pada Badan Pendapatan Pengelolaan Kuangan dan Aset Daerah Kota Probolinggo - Achmad Lodry Maspaitela; Joni Hendra; Umi Rahma Dhany (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This study aims to determine whether the influence of Budget Planning, Budget Execution, and Accuracy of Cash Planning has a simultaneous and partial effect on the Level of Budget Absorption at BPPKAD probolinggo city. And also among these three variables, which variable has the most dominant effect on the dependent variable (Budget Absorption Rate). The type of research used is descriptive quantitative, with the variables Budget Planning, Budget Execution, and Cash Planning Accuracy, the number of samples in this study were 76 respondents. The test results show that it partially affects the level of budget absorption at BPPKAD probolinggo city. The partial test results show that budget planning (X1), budget execution (X2), and cash planning accuracy (X3) of the three variables have significant values. Thus the results of the t (partial) test show that there is a positive and significant influence of variable budget planning budget execution and cash planning accuracy on the level of budget uptake at BPPKAD, City of Probolinggo.